Decreased circulating myeloid-derived suppressor cell count at the engraftment is one of the risk factors for multiple myeloma relapse after autologous hematopoietic stem cell transplantation - Tamara Tyrinova; Egor Batorov; Tatyana Aristova; Galina Ushakova; Svetlana Sizikova; Vera Denisova; Elena Chernykh (Heliyon, 2024)
Recent studies demonstrated that myeloid-derived suppressor cells (MDSCs) are involved in the pathogenesis and progression of multiple myeloma (MM). Nevertheless, data on the quantitative and functional changes in MDSCs during standard MM treatment remain poorly understood. Here, we determined that monocytic MDSCs (M-MDSC; CD14+HLA-DRlow/–) and granulocytic MDSCs (PMN-MDSC; Lin–HLA-DR–CD33+CD66b+) in MM patients in remission following induction therapy (IT) were significantly increased, while early MDSCs (E-MDSCs; Lin–HLA-DR–CD33+CD66b–) were decreased compared to the donor group. In progression, MM patients had the most pronounced decrease in E-MDSCs and enhanced levels of PMN-MDSCs. IT was accompanied with a decrease in the expression of arginase-1 (Arg-1). In MM patients with relapse or resistance to IT, Arg-1+ cell frequency in M-MDSCs and E-MDSCs, as well as PD-L1+ M-MDSCs, was increased, which may facilitate tumor immunosuppression. G-CSF administration led to a significant increment in the MDSC subsets. At the engraftment, circulating M-MDSC and PMN-MDSCs were temporarily increased, with a gradual decline to the pre-transplant levels in 12 months. The percentage of E-MDSCs was decreased at the leukocyte recovery. Patients with a higher (>Me) M-MDSC count at the engraftment had a shorter post-transplant leukopenia duration (Me 11 vs. 13 days; pU = 0.0086). The advanced MM stage, depth of response, and lower relative count of circulating E-MDSCs at the engraftment were independent risk factors associated with a lower progression-free survival.The obtained data allow us to hypothesize that MDSCs may play a positive role at the stage of leukocyte recovery by ameliorating the long-term anti-tumor response in MM.